2021
DOI: 10.3389/fvets.2021.660934
|View full text |Cite
|
Sign up to set email alerts
|

The Dispensable Surplus Dairy Calf: Is This Issue a “Wicked Problem” and Where Do We Go From Here?

Abstract: Surplus dairy calves consist of all dairy bull calves and any heifer calves not needed as replacements for the milking herd. The fate of these surplus calves varies by region; for example, in Australia and New Zealand they are often sold as “bobby” calves and slaughtered within the first weeks of life; whereas, in North America they are normally sold within the first weeks of life but reared for 16–18 weeks as veal or longer as dairy beef. Regardless of region, demand for these calves is often very low, drivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 83 publications
0
51
0
Order By: Relevance
“…Specific research gaps we report on within each research area were identified by the Scientific and Code Development Committees during numerous meetings over the course of the 3-year Code development process, using both their own extensive reviews of the literature and their collective expertise spanning long research careers in fish physiology and aquaculture [see the Scientific Committee's membership, detailed in (21)] and as aquatic veterinarians and aquaculture professionals (see the Code Development Committee's membership in the Code available at: https://www.nfacc.ca/codes-of-practice/ farmed-salmonids). Similar approaches that incorporate multiple perspectives from a variety of stakeholders have been encouraged in the field of animal welfare [e.g., (18,23,24)]. Importantly, we do not attempt to provide a comprehensive review of current salmonid welfare research nor a value judgment on what the most pressing future welfare research priorities are.…”
Section: Objective and Identification Of Research Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific research gaps we report on within each research area were identified by the Scientific and Code Development Committees during numerous meetings over the course of the 3-year Code development process, using both their own extensive reviews of the literature and their collective expertise spanning long research careers in fish physiology and aquaculture [see the Scientific Committee's membership, detailed in (21)] and as aquatic veterinarians and aquaculture professionals (see the Code Development Committee's membership in the Code available at: https://www.nfacc.ca/codes-of-practice/ farmed-salmonids). Similar approaches that incorporate multiple perspectives from a variety of stakeholders have been encouraged in the field of animal welfare [e.g., (18,23,24)]. Importantly, we do not attempt to provide a comprehensive review of current salmonid welfare research nor a value judgment on what the most pressing future welfare research priorities are.…”
Section: Objective and Identification Of Research Gapsmentioning
confidence: 99%
“…Some valuable reports like this already exist, such as the gap analysis study conducted by the Standing Committee on Agricultural Research [SCAR: (178)], and narrative reviews on various relevant topics by Ashley ( 6 180), among others. However, since the aquaculture industry includes a variety of expert stakeholders hailing from different backgrounds, we also recommend borrowing methods from the social sciences [e.g., a systematic review of text and opinion (181), survey-based research (182): Chapter 9], and/or participatory methods [discussed in (24)] to help reveal important anecdotal or experiential understanding from working aquaculture professionals that could inform novel research questions or policy developments [as suggested in relation to the issue of surplus dairy calves, by (24)].…”
Section: Future Directionsmentioning
confidence: 99%
“…Other perceived deterrents internationally to non-replacement male calf production are perceptions around a lack of obvious saleable markets (8), the perception of the replacement calf as a "low value byproduct" (9) and the limited number of rearing facilities for non-replacement male calves available to take non-replacement male calves for rearing (10). These compounding issues have resulted in the production of non-replacement male calves being identified as a "health and welfare challenge" internationally (8) and a "wicked problem, " namely a problem that is subject to real world constraints and with potentially multiple solutions, for the dairy industry in Australia (11).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, consumer opinion is driving practice change (14), with the general perception that calves should be productive as vealers, or slaughtered as mature cattle sold as "dairy beef " (15). Overcoming this issue has been describes as "inherently complex" due to evolving social culture, no ultimate defined solution, stakeholder expectations and producers achieving desired production goals (11). Therefore, understanding producer limitations and adoption of novel practices to manage male calves should present an economically viable option to retain these calves in the beef supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, much fewer male kids (buck kids) are raised to serve reproduction, resulting in a surplus number of male offspring. Similar to other agricultural sectors specialized on female derived products (dairy, eggs), practical and ethical issues arise as there are only limited purposes for surplus male offspring (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%